(untitled) (American Journal of Islam and Society, 1998)
A three-day international seminar jointly organized by the Department of Psychology, International Islamic University Malaysia (IIUM) and the International Institute of Islamic Thought Malaysia (IIITM) was held August 15-17, 1997, in Kuala Lumpur, Malaysia. Inaugurating the seminar, the Honomble Rector Dr. AbdulHamid A. AbuSulayman expressed happiness with the number of participants who are trying to look at human problems from an Islamic perspective. He said that intense research and hard work are needed to establish an Islamic framework of understanding human behavior and that scholars should not be impatient during this process. He reminded the participants that Muslim psychologists derive their understanding from the Qur’an and the Sunnah and that therefore their vision is different from other psychologists and counselors. He also said that Muslim psychologists have to delve deeply into themselves to gain self-understanding and selfstrength before they can help others. The conference was marked by keynote addresses that were delivered by renowned Muslim psychologists from around the world. Dr. Malik Badri of Sudan highlighted the achievements and discoveries of early Muslim scholars in the field of psychotherapy. He pointed out that Ibn Sina explained the learning of adaptive and maladaptive behavior on the basis of associative learning principles. He said that Ibn Sina and Al-Ghazali also explicated the developments of feeling of revulsion toward n a h d and useful objects in terms of stimulus substitution similar to today’s conditioning concept. Dr. Badri further ...